Synthesis and cytotoxic characteristics displayed by a series of Ag(i)-, Au(i)- and Au(iii)-complexes supported by a common N-heterocyclic carbene. (26th July 2018) - Jhulki, Lalmohan; Dutta, Parul; Santra, Manas Kumar; Cardoso, Marlon H.; Oshiro, Karen G. N.; Franco, Octávio L.; Bertolasi, Valerio; Isab, Anvarhusein A.; Bielawski, Christopher W.; Dinda, Joydev
Abstract : The design, synthesis and anticancer properties of a series of Ag(i ), Au(i ) and Au(iii )–NHC complexes supported by pyridyl[1, 2- a ]2-acetylylphenylimidazol-3-ylidene are described. Abstract : The synthesis, structures and anticancer studies of a series of precious metal complexes supported by 1-methyl-2-(phenyl)imidazo[1, 5- a ]pyridine-2-ylidene (1 ) have been highlighted. The Ag(i ) (2 ), Au(i ) (3 ) and Au(iii ) (4 ) complexes were prepared using standard methods and characterized by a range of techniques, including NMR spectroscopy, X-ray crystallography and elemental analyses. The in vitro cytotoxicity activities displayed by2–4 were explored against human colon adenocarcinoma (HCT116), lung cancer (A549) and breast cancer (MCF7) cell lines. A series of assays showed that all of the complexes exhibited significant growth inhibition in the aforementioned cell lines. Inspection of the data collected revealed that the Au(i ) and Ag(i ) complexes were more potent than their Au(iii ) congener, a trend that was found to be consistent with molecular docking studies that utilized BCL-2 as a model as this protein regulates cell death through apoptosis.